SISTEM INFORMASI MONITORING PEMBUATAN SERAGAM PADA YAYASAN AL-FAJAR MATARAM - Rochullah, Aulia; Agitha, Nadiyasari; Ratnasari, Dwi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
The Al-Fajar Mataram Foundation, an integrated Islamic school that has levels from Kindergarten, Elementary, and Middle School, is facing problems in the process of loading student uniform data, which is still done manually. This process often causes delays, uncertainty, errors, and a lack of transparency for schools and parents regarding the status of uniform production. To overcome this, it is proposed to develop a "Web-Based Uniform Manufacturing Process Monitoring System" using the Prototype method. This method was chosen because it allows users to directly see and test the system from the early stages of development. This provides an opportunity for users to provide suggestions and input directly, which can then be used by developers to improve system features that they feel are lacking, bringing them into line with what is needed. With this system, data regarding the uniform-making process can be managed more easily, making it easier to send data to tailors and allowing parents to monitor the status of their child's uniform-making directly. The results of testing using the Mean Opinion Score indicated a high level of user acceptance, with a User Acceptance Test score of 87.8%. This suggests that the system is highly beneficial for users.